Characterization of an NaCl-sensitive Staphylococcus aureus mutant and rescue of the NaCl-sensitive phenotype by glycine betaine but not by other compatible solutes. - Vijaranakul, U (1997)
To further study mechanisms of coping with osmotic stress-low water activity, mutants of Staphylococcus aureus with transposon Tn917-lacZ-induced NaCl sensitivity were selected for impaired ability to grow on solid defined medium containing 2 M NaCl. Southern hybridization experiments showed that NaCl-sensitive mutants had a single copy of the transposon inserted into a DNA fragment of the same size in each mutant. These NaCl-sensitive mutants had an extremely long lag phase (60 to 70 h) in defined medium containing 2.5 M NaCl. The osmoprotectants glycine betaine and choline (which is oxidized to glycine betaine) dramatically shortened the lag phase, whereas L-proline and proline betaine, which are effective osmoprotectants for the wild type, were ineffective. Electron microscopic observations of the NaCl-sensitive mutant under NaCl stress conditions revealed large, pseudomulticellular cells similar to those observed previously in the wild type under the same conditions. Glycine betaine, but not L-proline, corrected the morphological abnormalities. Studies of the uptake of L-[14C]proline and [14C]glycine betaine upon osmotic upshock revealed that the mutant was not defective in the uptake of either osmoprotectant. Comparison of pool K+, amino acid, and glycine betaine levels under NaCl stress conditions in the mutant and the wild type revealed no striking differences. Glycine betaine appears to have additional beneficial effects on NaCl-stressed cells beyond those of other osmoprotectants. The NaCl stress protein responses of the wild type and the NaCl-sensitive mutant were characterized and compared by labeling with L-[35 S]methionine and two-dimensional gel electrophoresis. The synthesis of 10 proteins increased in the wild type in response to NaCl stress, whereas the synthesis of these 10 proteins plus 2 others increased in response to NaCl stress in the NaCl-sensitive mutant. Five proteins, three of which were NaCl stress proteins, were produced in elevated amounts in the NaCl-sensitive mutant under unstressed conditions compared to the wild type. The presence of glycine betaine during NaCl stress decreased the production of three NaCl stress proteins in the mutant versus one in the wild type.